PENINGKATAN PENGETAHUAN HUKUM PERJANJIAN KERJA DI DESA MEKAR BUANA KABUPATEN KARAWANG - Suprayogi, Agus; Olivia, Fitria; Arianto, Henry; Ernawati, Ernawati; Baharudin, Erwan (Universitas Esa Unggul, 2020)
AbstractLegal protection for workers is the fulfillment of the basic rights inherent and protected by the constitution as regulated in Article 27 paragraph (2) of the 1945 Constitution